(untitled) (Research, Society and Development, 2022)
Given the importance of nutritional monitoring in childhood, this study has as its main objective to evaluate the nutritional status of children aged 0 to 5 years in the last five years in the state of Piauí, using data available in the Food and Nutritional Surveillance System (SISVAN). It is a descriptive cross-sectional study that evaluated 2,397,238 children under five years of age in the state of Piauí monitored by SISVAN between the years 2017 and 2021, according to the indices: Weight/Age, Weight/Height, Height /Age and Body Mass Index (BMI)/Age. Between 2018 and 2019, there was a greater number of attendances, mainly of male children, with a prevailing state of eutrophy in all indices. However, there were significant prevalence percentages for high weight for age (7.0% to 9.4%), low weight for age (1.0% to 3.4%), thinness (2.3% to 3.5%), age-related overweight and obesity (2.3% to 3.5%), overweight risk (15.6% to 17.9%) by BMI/age index and short height for age (greater than 12%). It is concluded that there was a higher prevalence of eutrophic nutritional status for all anthropometric indices evaluated, emphasizing the prevalence of nutritional status related to thinness, overweight and obesity in the studied population. With this, the need for more effective public policies for health promotion and more continuous nutritional surveillance is highlighted.